Análisis semiótico de las caricaturas de Vilmatraca publicadas en su Fan Page, periodo enero- junio 2021. - Inga Illicachi, Rubén Darío (2023)
The present research project is entitled “Semiotic Analysis of Vilmatraca’s fan page cartoons, period January – June 2021”. The main objective is to analyze Vilma Vargas’s “Vilmatraca” cartoons, their structure, form, and, content, which allows for constructing communication, to give meaning and value to the cartoons, as the objects to be analyzed in the project. As well, it is pretended to analyze the cartoons’ meaning and interpretation published on Vilmatraca’s fan page between January – June 2021. The research project is based on the structuralist theory of communication, it is settled in political communication, semiotics, Web 2.0, and digital platforms. It has employed the scientific method and the qualitative type of research which allows to identify the form of how the cartoons are interpreted and produced in the field of communication in social contexts. The research sample is done of 115 Vilmatraca’s fan page posts, posted in a 6-month period, for those it has been taken into account indicators such as graphic and literacy content, as well as the fan page users. Likewise, it has been employed different techniques and instruments as communication analysis, semiotic matrix analysis, and interviews.